CFD simulation on the thermal comfort in a library building in the tropics - Yau, Y.H.; Ghazali, N.N.N.; Badarudin, A.; Goh, F.C. (2009)
This paper presents a three-dimensional analysis for thermal comfort in a library. The room model includes library layout, equipment and peripheral positions as well as the positions of inlet and outlet air for IAQ controls. Cold clean air is supplied to the room through ceiling-mounted air grilles and exhausted through air grilles situated on the same ceiling. A commercial CFD package was used in this study to achieve solutions of the distribution of airflow velocity and temperature. Using high quality meshes is vital to the overall accuracy of the results. Simulation results show a good agreement with experimental data from the literature. This study has thoroughly analysed the indoor thermal conditions and airflow characteristics of the building. In addition, verification of the CFD program with experimental data showed that the program can provide reasonable and reliable predictions on thermal comfort performance with the help of precise boundary conditions.